Synthesis and Biological Activity of Hydrazones of o- and p-Hydroxybenzoic Acids. Spatial Structure of 5-Bromo-2-hydroxybenzylidene-4-hydroxybenzohydrazide - Nurkenov, O. A.; Satpaeva, Zh. B.; Schepetkin, I. A.; Khlebnikov, A. I.; Turdybekov, K. M.; Seilkhanov, T. M.; Fazylov, S. D. (MAIK NAUKA/INTERPERIODICA/SPRINGER, 233 SPRING ST, NEW YORK, 2017)
A series of hydrazones based on hydrazides of o- and p-hydroxybenzoic acids have been prepared. N-(5-Bromo-2-hydroxybenzylidene)-4-hydroxybenzohydrazide has been studied by X-ray diffraction analysis;its molecule forms hydrogen bond with a solvating ethanol molecule. Biological activity of the synthesizedhydrazones towards cathepsin Е and(or) elastase of human neutrophils has been determined.
Keywords: hydrazone; hydroxybenzoic acid hydrazide; cathepsin Е; neutrophil elastase; molecular docking